Penerapan Model Pembelajaran Kooperatif Tipe Snowball throwing dan diiringi Teka-Teki Silang Pada Pembelajaran Statistik STKIP Muhammadiyah Bungo - Nurlev Avana (Universitas Muhammadiyah Muara Bungo, 2018)
There are some factors affect the low result of learning Math, one of them is the students are not serious in studying, and the students' activity in learning is still less. The group works given by the teacher are only done by the smart students in the group, while the other group members do not do anything. To overcome this problem, one of the models that can be implemented is the cooperative learning using Snowball Throwing with the crossword puzzle.After conducting the observation during the class by implementing the cooperative learning using snowball throwing and crossword puzzle, it was found that there was an improvement of learning activity at the experiment classroom.Based on the result from both of experiment and control groups, after doing the hypothesis test at α = 0,05, it was found and . because t > t , so the hypothesis was proved that the result of studying at the group with the implementation of cooperative learning using snowball and crossword puzzle is better than the group with a conventional way.